EVALUATING IMPACT OF SUSTAINABILITY PRACTICES AND OPERATIONAL EFFICIENCY ON FIRM VALUE IN INDONESIA’S MINING SECTOR - Windyasari, Erika; Bustaman, Yosman (UI Scholars Hub, 2026)
Sustainability practices are increasingly prominent in investor assessments of firm value Nevertheless, empirical evidence regarding which specific environmental practices are incorporated into capital market valuations remains inconclusive, particularly within mining sectors in emerging markets. This study investigates the correlation between sustainability practices energy efficiency, water management, waste management, renewable energy adoption and environmental quality (PROPER rating) together with operational efficiency and firm value in Indonesian listed mining firms. The analysis uses panel data for 23 firms over 2017–2023. Firm value is measured by Tobin’s Q, while operational efficiency is measured using Data Envelopment Analysis (DEA). The correlation is estimated using panel regression models. The results show that renewable energy adoption is the only sustainability practice which positively and significantly correlated with firm value (β=1.2026, p=0.0227). Firm size is also positively correlated with Tobin’s Q (β=0.4195, p<0.001). However, energy efficiency, water management, waste management, environmental quality (PROPER rating) and DEA based operational efficiency are not significantly correlated with firm value in the observed period. These findings indicate that capital markets place higher weight on strategic sustainability commitments, particularly energy transition than on incremental operational improvements. By disaggregating sustainability dimensions and incorporating efficiency measures, this study contributes to the literature on sustainability firm value correlates in resource-based industries within emerging markets. The results imply that while renewable energy investments may be more reflected in market valuation, other environmental and efficiency related practices may require longer time horizons or stronger disclosure mechanisms to be recognized by investors. Enhancing the credibility of sustainability reporting may therefore improve the alignment between firm performance and market perception.